2022
DOI: 10.1007/s11356-022-22911-2
|View full text |Cite
|
Sign up to set email alerts
|

The human well-being and environmental degradation nexus in Africa

Abstract: Environmental degradation continues to attract interest from academics, policymakers, and other stakeholders. However, empirical studies have been limited, particularly in the choice of human well-being indicators.Therefore, this study extends the literature by broadening the nexus between human well-being and environmental degradation in 29 African countries from 1970 to 2019. Preliminary tests adaptable to effects of cross-sectional dependency and heterogeneity in panel dataset were adopted, alongside the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Similarly, Aladejare (2022b) demonstrated with the fixed and random effect, feasible generalised least squares (FGLS) and AMG methodologies; and found that natural resource rents worsened ecological sustainability for the five wealthiest African countries. In a related study, Aladejare (2023c) applied the CS-ARDL approach and revealed that natural resource wealth promotes ecological atrophy in 29 African economies. Alola et al (2019) demonstrated with the ARDL technique that high inflation episodes in coastline Mediterranean countries enhance ecological sustainability.…”
Section: Empirical Review 231 Resources Income and Sustainable Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Aladejare (2022b) demonstrated with the fixed and random effect, feasible generalised least squares (FGLS) and AMG methodologies; and found that natural resource rents worsened ecological sustainability for the five wealthiest African countries. In a related study, Aladejare (2023c) applied the CS-ARDL approach and revealed that natural resource wealth promotes ecological atrophy in 29 African economies. Alola et al (2019) demonstrated with the ARDL technique that high inflation episodes in coastline Mediterranean countries enhance ecological sustainability.…”
Section: Empirical Review 231 Resources Income and Sustainable Develo...mentioning
confidence: 99%
“…From the neoliberal perspective, globalisation has been a blessing than a curse, especially from the lens of depreciating poverty and income inequality in developing nations (Aladejare and Nyiputen, 2022;Adjei and Adu-Gyamfi, 2022). However, globalisation is also believed to have aided developing countries' accelerated ecological deterioration through the transfer of "dirty technology" from the developed world (Le and Ozturk, 2020;Nathaniel et al, 2021;Aladejare, 2023c).…”
Section: Introductionmentioning
confidence: 99%
“…However, the saving-investment gap in developing countries is a clog in providing the amenities required for a better life. Consequently, countries often rely on foreign debt to augment their capital shortfall in the condition of the needed infrastructures for an enhanced QoL (Aladejare, 2022;Khan et al, 2022;Aladejare, 2023b). Also, most developing economies are characterised by a limited fiscal space deficient in meeting their development needs (OECD, 2020); hence, debt financing continues to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the contemporaneous impact of these indicators on QoL are scarce, particularly for developing and emerging economies. Specifically, most Africanrelated literature has dwelled on income, healthcare, and ecological determinants (Sarkodie and Adams, 2020;Cavusoglu and Gimba, 2021;Omokanmi et al, 2022;Mahalik et al, 2022;Aladejare, 2023b). However, the roles of renewable energy, urbanisation, and external debt alongside those above are seldom considered in QoL improvement in the continent.…”
Section: Introductionmentioning
confidence: 99%
“…From the neoliberal perspective, globalisation has been a blessing than a curse, especially from the lens of depreciating poverty and income inequality in developing nations (Aladejare and Nyiputen, 2022;Adjei and Adu-Gyamfi, 2022). However, globalisation is also believed to have aided developing countries' accelerated ecological deterioration through the transfer of "dirty technology" from the developed world (Le and Ozturk, 2020;Nathaniel, 2021;Hussain and Zhou, 2022;Aladejare, 2023c).…”
Section: Introductionmentioning
confidence: 99%